Professional Competency Mastering in 21st Century Teacher Performance Effectiveness in Elementary Schools - Sudarmin Sudarmin; Salmia Salmia; Andi Asdar (Universitas of Muhammadiyah Makassar, 2023)
This study aims to describe how the mastery of the professional competence of teachers in elementary schools, and how the effectiveness of the performance of 21st century teachers in elementary schools. This type of research is qualitative by analyzing the phenomenon and the meaning contained in the mastery of professional competence of teachers in the effectiveness of the performance of 21st century teachers in elementary schools . The data were collected through interviews, observation and documentation, then the data were analyzed using several steps of utilizing, categorizing, data intervention, then the data were validated by extending the time of observation and triangulation. The results of the study show that the mastery of professional competence in the effectiveness of teacher performance in the 21st century teachers have mastered the competence of the teaching profession namely pedagogical competence, social competence, professional competence, leadership competence, assessment competence, in all competencies possessed by a teacher must include abilities in the five the main domains, namely: knowledge, skills, attitudes, personality, and ethical values, with the mastery of the professional competence of teacher performance can help students become quality human beings and have noble character.